The Role of Teacher Supervision in Optimizing the Use of Supervision on the Teaching Freedom Platform - Vivi Irvana Safitri; Siti Ahidiyah; Tri Suranti; Cyntia Merystica; Chika Rahayu (Journal of Educational Research, Evaluation and Supervision, 2025)
This study aims to describe the role of supervision in supporting the optimization of the implementation of the independent training program through the Merdeka Teaching Platform (PMM). The research used a descriptive approach with data collection techniques in the form of a first cycle mentoring questionnaire filled out by two teachers. The research instrument involves six indicators which include teacher involvement in watching training videos, studying materials, completing modules, doing post-tests, completing real action sheets, and obtaining self-training certificates. The results showed that the first teacher obtained a final score of 91% with five indicators achieved, while the second teacher achieved a final score of 100% with all indicators achieved. Supervision played an important role in monitoring teachers' involvement in each stage of the training. These findings provide a concrete picture of the implementation of supervision in supporting the optimization of self-training in PMM.